Need Help?

Subscribe to Differential Equation

  • Notes
  • Comments & Questions

Consider the differential equation $$x^{2} y^{\prime \prime}+3 x y^{\prime}-3 y=\frac{12 x^{2}}{1+x^{2}}, x>0$$
Find two linearly independent solutions of the form $$x^{r}$$ to the
associated homogeneous differential equation
Find the general solutions of the given equation.

(a) If $$x^{r} $$ is asolution to the assectated homo $$-D \cdot E$$

$$y=x^{r} $$ is a solution

$$y^{\prime}=r x^{r-1} $$

$$y^{\prime \prime}=(r)(r-1) x^{r-2} $$ Substitute in the Homo. D.E:

$$x^{2}\left[(r)(r-1) x^{r-2}\right]+3 x\left[r x^{r-1}\right]-3 x^{r}=0$$

$$(r)(r-1) x^{r}+3 r x^{r}-3 x^{r}=0$$

$$\rightarrow x^{r}[r(r-1)+3 r-3]=0 \quad \div x^{r} $$

$$r^{2}-r+3 r-3=0 \rightarrow r^{2}+2 r-3=0$$



$$y=x^{-3}, y=x^{1} $$

$$x^{2} y^{\prime \prime}+3 x y^{\prime}-3 y=\frac{12 x^{2}}{1+x^{2}} \quad \div x^{2} $$

$$y^{\prime \prime}+\left(\frac{3}{x}\right) y^{\prime}-\left(\frac{3}{x^{2}}\right) y=\frac{12}{1+x^{2}} $$

\ $$y_{c}=c_{1} x+c_{2} {x}^{-3} $$

$$ y p=A_{1}(x) x+B(x) x^{-3} $$

$$A^{\prime} x+B^{\prime} {x}^{-3}=0 \longrightarrow (1)$$

$$A^{\prime}-3 B^{\prime} x^{-4}=\frac{12}{1+x^{2}} \longrightarrow (2)$$

$$-3 B^{\prime} {x}^{-4}=\frac{12}{1+x^{2}}$$ multiply by $$(-x)$$

$$3 {B^\prime} {x}^{-3}=\frac{-12 x}{1+x^{2}} \quad (1) + (2)$$

$$4 B^{\prime} x^{-3}=\frac{-12 x}{1+x^{2}} \quad \div 4 x^{-3} $$

$$B^{\prime}=\frac{-12 x}{1+x^{2}} \times \frac{1}{4 x^{-3}}=\frac{-3 x^{4}}{1+x^{2}}$$ in $$(1)$$

$$A^\prime x+B^\prime x^{-3}=0 \rightarrow A^\prime x+\left(\frac{-3 x^{4}}{1+x^{2}}\right) x^{-3}=0$$

$$ {A^\prime} x+\frac{-3 x}{1+x^{2}}=0 \Rightarrow A^{\prime}=\frac{+3 x}{1+x^{2}} * \frac{1}{x}=\frac{3}{1+x^{2}} $$

$$ A^{\prime}=\frac{3}{1+x^{2}} $$

$$A=\int \frac{3}{1+x^{2}} d x=3 \cdot \tan ^{-1}(x)$$

$$B=\int \frac{-3 x^{4}}{1+x^{2}} d x$$

$$=\int\left[-3 x^{2}+3 \frac{-3}{x^{2}+1}\right] d x$$

$$B=\frac{-3 x^{3}}{3}+3 x-3 \tan ^{-1} x$$

$$y p=A x+B x^{-3}=3x \tan ^{-1}(x)+\left(-x^{3}+3 x-3 \tan ^{-1}(x)\right) x^{-3} $$

$$y_{g . s}=y_{p}+y_{c}$$

No comments yet

Join the conversation

Join Notatee Today!